PENGARUH VARIASI KONSENTRASI GLISERIN TERHADAP SIFAT FISIK OBAT KUMUR EKSTRAK DAUN BELUNTAS (Pluchea indica L.) - MIKHANIA CHRISTININGTYAS ERYANI (AKADEMI FARMASI JEMBER, 2021)
Mouthwash is an aqueous solution used as a cleanser to improve oral health, aesthetics, and breath freshness. The purpose of this study was to determine the effect of variation concentration of glycerin in beluntas leaf extract (Pluchea indica L.) on the physical properties of mouthwash. Extraction was using maceration method with 5000 ml of 96% ethanol as a solvent. Beluntas leaf extract mouthwash was made in 3 formulas with different glycerin concentration which were 10% (F1), 15% (F2) and 20% (F3). Evaluation includes organoleptic, pH and viscosity tests. The organoleptic test of the mouthwash on the three formulations was brown in color, tasted slightly sweet and had a distinctive minty smell. pH of three formulas were 6.16 - 6.20. Data processing using One Way Anova showed that there was no effect of glycerin variations concentration to pH of mouthwash but there was an effect of glycerin variations concentration to the viscosity of mouthwash.